New Method for the On-Line Determination of Molybdenum Via New Microphotometric Home Mode Instrument, Using Hight Emitting Diode as a Variable Intensity Radiant Source with a Miniture Photosilicone Diode Detector for System: Molybdenum(VI)-Hydrogen Peroxide-Ammonium Solution (Baghdad Science Journal, 2025)
This research work aims to the determination of molybdenum (VI) ion via the formation of peroxy molybdenum compounds which has red-brown colour with absorbance wave length at 455nm for the system of ammonia solution-hydrogen peroxide-molybdenum (VI) using a completely newly developed microphotometer based on the ON-Line measurement. Variation of responses expressed in millivolt. A correlation coefficient of 0.9925 for the range of 2.5-150 ?g.ml-1 with percentage linearity of 98.50%. A detection limit of 0.25 ?g.ml-1 was obtained. All physical and chemical variable were optimized interferences of cation and anion were studied classical method of measurement were done and compared well with newly on-line measurements. Application for the use of developed method on alloy samples, using standard addition method and agreed quite wall.